Research on coal mine data management and service platform - Chen Yunqi (ITM Web of Conferences)
In order to solve the problems of massive data of multi-source heterogeneous systems in coal mines, such as complex types, difficult aggregation, poor quality, and lack of a unified service platform, this paper analyzes the key technologies and theoretical methods in data collection, transmission, storage, calculation and service, and designs a coal mine data and management service platform based on a multi-layer architecture. It clearly defines that the platform consists of main functional modules such as collection and access management, quality management, storage management, metadata and master data management, operation and maintenance management and visualization management, which provides unified data services for all businesses and systems in the mine, and further improves the level of coal mine intelligence.